The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/jnr.25205
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the causal relationship between blood pressure and regional white matter integrity: A two‐sample Mendelian randomization study

Abstract: Elevated arterial blood pressure (BP) is a common risk factor for cerebrovascular and cardiovascular diseases, but no causal relationship has been established between BP and cerebral white matter (WM) integrity. In this study, we performed a twosample Mendelian randomization (MR) analysis with individual-level data by defining two nonoverlapping sets of European ancestry individuals (genetics-exposure set: N = 203,111; mean age = 56.71 years, genetics-outcome set: N = 16,156; mean age = 54.61 years) from UK Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Moreover, diastolic blood pressure (DBP) was found to be the main contributing factor, instead of systolic blood pressure (SBP). Ye et al concentrated on FA measures for 39 regions and identified significantly negative causal effects of BP on 21 and 18 WM tracts for SBP and DBP, respectively ( Ye et al, 2023 ). Siedlinski et al conducted a comprehensive assessment, integrating data on SBP, DBP and pulse pressure (PP) with 3,935 BIDPs ( Siedlinski et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, diastolic blood pressure (DBP) was found to be the main contributing factor, instead of systolic blood pressure (SBP). Ye et al concentrated on FA measures for 39 regions and identified significantly negative causal effects of BP on 21 and 18 WM tracts for SBP and DBP, respectively ( Ye et al, 2023 ). Siedlinski et al conducted a comprehensive assessment, integrating data on SBP, DBP and pulse pressure (PP) with 3,935 BIDPs ( Siedlinski et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, there have been more debates and uncertainties surrounding the effect of DBP on brain structures and cognitive function compared with SBP [55,56]. Nevertheless, both genetically proxied and regular measurements of SBP and DBP have shown diverse causal effects or significant associations with various targets and regional effects related to white matter fractional anisotropy tracks, brain structures, white matter lesions, cortical volume, and cerebral blood flow [56][57][58][59]. The relationship between blood pressure and brain aging is complex, multifactorial [60], time-dependent, or even nonlinear [61].…”
Section: Discussionmentioning
confidence: 99%